Evaluasi Angkutan Pelajar di Kota Singkawang - Queeny Nirvana Mindy Kadsulatida; Said Said; Elsa Tri Mukti (Pusat riset dan Inovasi Nasional, 2026)
The city of Singkawang has experienced rapid population growth, leading to an increase in the number of students. On 17 September 2024, the Singkawang City Transportation Agency implemented a free revitalized Student Transport service to reduce the number of traffic accidents involving students. The aim of this study is to identify service and respondent characteristics, evaluate operational management, and assess performance and user satisfaction using the IPA and CSI methods, as well as Vehicle Operating Costs (VOC). The research employs a descriptive quantitative method by analyzing descriptive statistical data. Data were obtained from field observations, interviews, and surveys of 400 student respondents (146 users and 254 non-users). The results show that the student transport operates with two vehicles serving the North and East Singkawang routes. The load factor for outbound trips is 22%–32% and for return trips is 11%–12%, with travel times of 68–85 minutes, average operating speeds of 20–22 km/hour, and circulation times of 68–85 minutes. Based on the IPA analysis, the indicators in quadrant D require socialization regarding the functions and use of the interior of the student transport. The CSI result shows a score of 99.79% (very satisfied). The annual VOC amounts to IDR 292,905,814 (East Singkawang) and IDR 282,020,390 (North Singkawang). In conclusion, this service is satisfactory but still requires socialization to enhance its attractiveness and effectiveness.